The effect of chemical and organic fertilization on Phytoplankton and fish production in carp (Cyprinidae) polyculture system - Ponce-Palafox, J T (Revista Bio Ciencias, 2010)
This study reports the effects of sheep and pig liquid manure, and chemical fertilizer on the phytoplankton, primary productivity and aquaculture production in the cultivation of carp in semi-rustic ponds. The total yield was 4.632 kg in two hectares. Treatment with chemical fertilizers was found to present the highest yield with 10.06 ± 0.67 (kg/Ha/day), followed by treatment with pig manure (8.27± 1.24 kg/Ha/day) and sheep manure (6.33 ±1.95 kg/Ha/day). It was also found that concentrations of phytoplankton were significantly (p<0.05) higher in ponds fertilized with sheep and pig manure (945.940 and 1,157,706 cells/ml, respectively) than in ponds where chemical fertilizer was used (744.560 cells/ml). In general, conditions were adequate to obtain high yields without commercial feed, thus organic fertilizer application can be recommended because ofits availability and low cost.